2022
DOI: 10.1186/s12884-021-04324-0
|View full text |Cite
|
Sign up to set email alerts
|

Which chart and which cut-point: deciding on the INTERGROWTH, World Health Organization, or Hadlock fetal growth chart

Abstract: Objective To determine how various centile cut points on the INTERGROWTH-21st (INTERGROWTH), World Health Organization (WHO), and Hadlock fetal growth charts predict perinatal morbidity/mortality, and how this relates to choosing a fetal growth chart for clinical use. Methods We linked antenatal ultrasound measurements for fetuses > 28 weeks’ gestation from the British Columbia Women’s hospital ultrasound unit with the provincial perinatal datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
3
15
0
2
Order By: Relevance
“…Theoretically, such diagnoses could be used as inputs for improving obstetric and neonatal management in conjunction with other markers and pregnancy complications. However, as previous studies have shown 14,15,[23][24][25][26]36 and our study confirms, SGA or LGA diagnosis, when used in isolation without other predictors, performs poorly for predicting SNMM; in other words, the probability of SNMM (or neonatal death) is not materially changed by such a diagnosis. In our study, the expected risk of SNMM changed marginally from 20.2 per 1,000 live births to 23.8, 36.1 and 54.4 per 1,000 live births using a mild (10% increase in odds), moderate (50%) or extreme (100%) definition of SGA among female singletons at 39 weeks' gestation (Table 1).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Theoretically, such diagnoses could be used as inputs for improving obstetric and neonatal management in conjunction with other markers and pregnancy complications. However, as previous studies have shown 14,15,[23][24][25][26]36 and our study confirms, SGA or LGA diagnosis, when used in isolation without other predictors, performs poorly for predicting SNMM; in other words, the probability of SNMM (or neonatal death) is not materially changed by such a diagnosis. In our study, the expected risk of SNMM changed marginally from 20.2 per 1,000 live births to 23.8, 36.1 and 54.4 per 1,000 live births using a mild (10% increase in odds), moderate (50%) or extreme (100%) definition of SGA among female singletons at 39 weeks' gestation (Table 1).…”
Section: Discussionsupporting
confidence: 69%
“…Although the newly created normative/prescriptive Intergrowth 21 st Project and World Health Organization (WHO) birth weight-for-gestational age standards 1-4 represent a conceptual departure from previous descriptive, population-based references 5-11 and offer several theoretical advantages, studies comparing existing references and the new standards have not succeeded in establishing a preferred method for identifying SGA and LGA infants. 12-26…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los resultados presentados en cuanto a la capacidad predictiva son similares a la publicación de Molina et al 12 , quienes en un análisis secundario de un estudio prospectivo realizaron una validación de los criterios del consenso Delphi comparándolo con la definición de RCF de SMMF/ACOG, encontrando que ninguno de los dos criterios aporta un AUC aceptable para predicción de RANC: 0,50 (IC 95 %: 0,48-0,53) y 0,53 (IC 95 %: 0,50-0,55) para SMMF/ACOG y consenso Delphi. Resultados, a su vez, consistentes con los encontrados por Liauw et al 16 ; AUC: 0,54 para predicción de RANC con fetos menores al percentil 10 de crecimiento. Por otra parte, los hallazgos de baja sensibilidad para predicción de RANC encontrados en el presente estudio son similares a los informados por Roeckner et al 17 , con una sensibilidad de 15,1 % y de 10,1 % para SMMF/ACOG y consenso Delphi, respectivamente.…”
Section: Discussionunclassified
“…En una investigación en la que se compara pre maturidad y RCIU en mujeres con eclampsia y mujeres con síndrome HELLP, se encontró 66,6% de prematuridad en síndrome HELLP vs 0% en eclampsia y RCIU con per centil menor de 3 %, en eclampsia 16,7% vs 26,6% en síndrome HELLP; además muerte perinatal en 11,1% de síndrome HELLP vs 0 % en eclampsia [109]. [110,111].…”
Section: Manejounclassified